Pembuatan Logo Untuk UMKM Ibu Vivi di Desa Weru Lor - Haikal Avicenna; Dinda Rizka Yunita; Aris Riyanto; Muhammad Furqon (Darma Abdi Karya, 2024)
This study aims to design and develop a logo for the SME "Warung Ibu Vivi" located in Weru Lor as part of an effort to enhance its visual identity and competitiveness. In today's globalized era, having a strong and appealing visual identity is essential for any business, including SMEs, to attract consumer attention and distinguish itself from competitors. The methods used in this service project include needs analysis, logo creation, finalization, and implementation. The design process involves active participation from the business owner to ensure that the logo aligns with the vision and values of "Warung Ibu Vivi". The final output of this project is a logo that effectively represents the SME's identity and a banner that incorporates the new logo. The new logo and banner are expected to improve brand awareness and increase the appeal of "Warung Ibu Vivi" to potential customers, thereby contributing to increased sales and business growth.